The gut microbiome, mild cognitive impairment, and probiotics: A randomized clinical trial in middle-aged and older adults - Aljumaah, Mashael R.; Bhatia, Urja; Roach, Jeffery; Gunstad, John; Azcarate Peril, M. Andrea (Clinical nutrition (Edinburgh, Scotland), 2022)
Advancing age coincides with changes in the gut microbiome and a decline in cognitive ability. Psychobiotics are microbiota-targeted interventions that can result in mental health benefits and protect the aging brain. This study investigated the gut microbiome composition and predicted microbial functional pathways of middle-aged and older adults that met criteria for mild cognitive impairment (MCI), compared to neurologically healthy individuals, and investigated the impact of probiotic Lactobacillus rhamnosus GG (LGG) in a double-blind, placebo-controlled, randomized clinical trial. A total of 169 community-dwelling middle-aged (52–59 years) and older adults (60–75 years) received a three-month intervention and were randomized to probiotic and placebo groups. Participants were further subdivided based on cognitive status into groups with intact or impaired cognition and samples were collected at baseline and post supplementation. Microbiome analysis identified Prevotella ruminicola, Bacteroides thetaiotaomicron, and Bacteroides xylanisolvens as taxa correlated with MCI. Differential abundance analysis at baseline identified Prevotella as significantly more prevalent in MCI subjects compared to cognitively intact subjects (ALDEx2 P = 0.0017, ANCOM-BC P = 0.0004). A decrease in the relative abundance of the genus Prevotella and Dehalobacterium in response to LGG supplementation in the MCI group was correlated with an improved cognitive score. Our study points to specific members of the gut microbiota correlated with cognitive performance in middle-aged and older adults. Should findings be replicated, these taxa could be used as key early indicators of MCI and manipulated by probiotics, prebiotics, and symbiotics to promote successful cognitive aging. Registered under ClinicalTrials.gov Identifier no. NCT03080818. [Display omitted]